2021
DOI: 10.1038/s41598-021-80962-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of staging and risk factors with cardiovascular autonomic neuropathy in patients with type II diabetes mellitus

Abstract: The impairment of cardiovascular autonomic control among the underdiagnosed complication of diabetes mellitus (DM) with a high prevalence rate of up to 60% in type 2 DM (T2DM). Cardiac autonomic neuropathy (CAN) is an independent risk factor for cardiovascular mortality, arrhythmia, silent ischemia, any major cardiovascular event, and heart failure. We aimed to evaluate cardiovascular autonomic activity by different physiological maneuvers, study risk factors for diabetic CAN including age, gender, duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
3
1
Order By: Relevance
“…Among the traditional CVD risk factors, BMI was one of the reported factors associated with CAN. In the current study, the absence of association between BMI or body fats percentage with CAN is perhaps due to the smaller sample size from other studies, which reported an inverse association [29,31,40]. This also applies to other CVD risk factors such as age and body fats percentage.…”
Section: Discussioncontrasting
confidence: 65%
“…Among the traditional CVD risk factors, BMI was one of the reported factors associated with CAN. In the current study, the absence of association between BMI or body fats percentage with CAN is perhaps due to the smaller sample size from other studies, which reported an inverse association [29,31,40]. This also applies to other CVD risk factors such as age and body fats percentage.…”
Section: Discussioncontrasting
confidence: 65%
“…Despite the passage of time, the performing of state-ofthe-art ANS tests has not changed. In the latest papers using Ewing's tests [17][18][19][20][21][22] we found the same problems as mentioned previously: varying protocols, different stimulus level or tests' order. However, it is satisfactory that in almost every paper (besides one 17 ) level and duration of stimulus are mentioned.…”
Section: Methods Of Stimulus Control In Ewing's Batterysupporting
confidence: 66%
“…However, it is satisfactory that in almost every paper (besides one 17 ) level and duration of stimulus are mentioned. Only in a few papers [18][19][20] were types of device used to control stimulus mentioned in general terms, eg, aneroid manometer. None of these papers mention method of controlling stimulus.…”
Section: Methods Of Stimulus Control In Ewing's Batterymentioning
confidence: 99%
“…Overall, the prevalence of CAN has been variably reported from 10%–80%. [ 6 7 8 9 10 ] Most of the studies are consistent regarding close association of diabetic peripheral neuropathy and CAN. There is being an increasingly recognized association between peripheral neuropathy and CAN in patients of type 2 DM.…”
Section: Introductionmentioning
confidence: 68%